The Influence of Accountability, Website Security, and Social Influence on Donation Intention in Crowdfunding: The Mediating Role of Trust - Nurul Aini Br Purba; Moh Shadam Taqiyyuddin Azka; Hilmy Baroroh (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
Purpose: This study aims to examine the influence of accountability, website security, and social influence on donation intentions in “Dompet Dhuafa” crowdfunding, with trust serving as a mediating variable. Method: This is a quantitative study, utilising data collection through a questionnaire. The sampling technique employed was non-probability sampling, with a total of 130 respondents, all of whom were young Muslim individuals. This group was chosen due to their growing engagement with digital platforms and their increasing role as active donors in online Islamic philanthropy. Focusing on young Muslims also distinguishes this study from previous research, which often overlooks age-specific behavioural dynamics in crowdfunding contexts. The research was analysed using the Partial Least Square-Structural Equation Modelling (PLS-SEM) approach with the aid of the SmartPLS 4 analytical tool. Finding: The results showed that accountability and website security have a significant direct effect on donation intentions and trust, while social influence does not affect donation intentions but has a significant impact on trust. Based on the indirect effect test, trust was found to mediate the relationship between accountability, website security, social influence, and donation intentions. Novelty: These findings will create a gap that will be evaluated for consistency in elucidating their impact on an individual's intention to donate online.